PELATIHAN AKUNTANSI DAPAT MENINGKATKAN KINERJA WIRAUSAHA - Satiman Satiman; Suparmin Suparmin; Edon Ramdani; Maharani Maharani; Rahma Wiyanti (Abdimisi, 2019)
The purpose of this community service is to provide accounting training for the children of the Al-Kamilah Foundation in the form of financial reporting, BEP calculations, etc. so that they are enthusiastic in establishing an independent business. The method of community service is training, seminars, and discussions. The population in this community service activity is 100 children who are under the auspices of the Al-Kamilah Pamulang Foundation. The result of this community service is that all participants can apply accounting theory in their efforts. Keywords: Accounting Training, Entrepreneurship